Community Social Cohesion During a Large Public Housing and Neighborhood Redevelopment: A Mixed Methods Study - Judith L. Perrigo; Anna Ginther; Haniya S. Syeda; Victoria Shier; Ashlesha Datar (Societies)
Public housing redevelopments can disrupt community members’ sense of belonging and attachment to their neighborhood, in large part due to resident displacement and gentrification. Recent public housing redevelopment efforts seek to mitigate these adverse changes, but evidence of their association with community social cohesion is limited. The current mixed methods study examines community social cohesion from different perspectives during a large public housing and neighborhood redevelopment in Southern California. Semi-structured qualitative interviews (n = 21) were conducted with various community stakeholders to explore their perceptions of social cohesion within the context of public housing and neighborhood redevelopment. Additionally, the Social Cohesion scale was used to evaluate residents’ (n = 647) sense of neighborhood social cohesion. Stakeholders raised concerns about how redevelopment could disrupt the social fabric of their communities and underscored the importance of deliberate efforts to promote integration between existing and incoming residents. The significance of creating physical spaces, protecting landmarks, and facilitating social interaction to cultivate a sense of belonging was also emphasized. Residents of the public housing redevelopment reported significantly higher levels of social cohesion when compared to residents from two neighboring public housing complexes that are not undergoing redevelopment. Implications for public housing redevelopment strategies, community integration efforts, and future research are discussed.